2022
DOI: 10.1002/btm2.10349
|View full text |Cite
|
Sign up to set email alerts
|

Turning adversity into opportunity: Small extracellular vesicles as nanocarriers for tumor‐associated macrophages re‐education

Abstract: Currently, small extracellular vesicles (sEV) as a nanoscale drug delivery system, are undergoing biotechnological scaling and clinical validation. Nonetheless, preclinical pharmacokinetic studies revealed that sEV are predominantly uptaken by macrophages. Although this “sEV‐macrophage” propensity represents a disadvantage in terms of sEV targeting and their bioavailability as nanocarriers, it also represents a strategic advantage for those therapies that involve macrophages. Such is the case of tumor‐associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 220 publications
0
4
0
Order By: Relevance
“…TAMs were divided into two phenotypes: tumor-suppressing M1 macrophages and tumor-promoting M2 macrophages. In general, TME promotes the functionality of TAMs into M2 phenotypes, and M2 macrophages produce immunosuppressive cytokines to facilitate tumor progression ( 145 ). In contrast, M1 macrophages are activated by pro-inflammatory cytokines, resulting in tumor suppression ( 146 ).…”
Section: Exos As Drug Delivery Carrier For Cancer Immunotherapymentioning
confidence: 99%
“…TAMs were divided into two phenotypes: tumor-suppressing M1 macrophages and tumor-promoting M2 macrophages. In general, TME promotes the functionality of TAMs into M2 phenotypes, and M2 macrophages produce immunosuppressive cytokines to facilitate tumor progression ( 145 ). In contrast, M1 macrophages are activated by pro-inflammatory cytokines, resulting in tumor suppression ( 146 ).…”
Section: Exos As Drug Delivery Carrier For Cancer Immunotherapymentioning
confidence: 99%
“…This immunological effect mediated by macrophages after sEVs injection is widely described in the literature since the significant clearance of sEVs in systemic circulation occurs through these myeloid cells [ 17 , 50 , 51 , 52 ]. Peyer’s patches (PPs) are subepithelial lymphoid follicles present in the intestine greatly enriched in innate and adaptive immune cells [ 53 ].…”
Section: Cellular and Molecular Mediators For Sevs Uptake After Oral ...mentioning
confidence: 99%
“…Cell membranes-derived exosomes (also called as small extracellular vesicles) can also be used as nanomaterials for immunotherapy. Dario et al have indicated that these exosomes can be significantly uptaken by macrophages, which means that this class of nanocarrier has a certain potential for TAMs targeting 124 . Hence, the application of exosomes as nanocarriers of TAMs reprogramming molecules can effectively repolarize an immunostimulatory M1-phenotype.…”
Section: Rational Design Of Tams-focused Functional Nanomedicinesmentioning
confidence: 99%